2020
DOI: 10.1590/0001-3765202020190134
|View full text |Cite
|
Sign up to set email alerts
|

Development of nanoparticles coated with cassava bagasse pectin (Manihot esculenta Crantz) containing β-carotene for mucoadhesive applications

Abstract: Pectin (PC) extracted from a solid residue from cassava roots (Manihot esculenta Crantz) was used to coat nanoparticles (NP) containing β-carotene (BC) aiming at the gastrointestinal administration of this lipophilic nutraceutical. The NP were prepared by spontaneous emulsifi cation method using food grade components. Pectincoated NP have been successfully prepared as confi rmed by the increased particle size and negative surface charges due to the pectin's anionic nature. NP showed spherical shape and monodis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In another investigation, pectin nanoparticles were created utilizing food-grade cassava root material to coat the nutritional supplement β-carotene, with the goal of increasing the bioavailability of these lipophilic dietary nutraceuticals during gastrointestinal (GI) delivery. The particles have a mean size of 21.3 nm, are mucoadhesive, and have enhanced antioxidant activity, bioavailability, and stability up to 90 days at 4°C [81]. Researchers developed caseinate/pectin-based phytosterol nanoparticles by combining emulsification, evaporation, and complex coacervation processes.…”
Section: Pectin-based Micro/nanoparticlesmentioning
confidence: 99%
“…In another investigation, pectin nanoparticles were created utilizing food-grade cassava root material to coat the nutritional supplement β-carotene, with the goal of increasing the bioavailability of these lipophilic dietary nutraceuticals during gastrointestinal (GI) delivery. The particles have a mean size of 21.3 nm, are mucoadhesive, and have enhanced antioxidant activity, bioavailability, and stability up to 90 days at 4°C [81]. Researchers developed caseinate/pectin-based phytosterol nanoparticles by combining emulsification, evaporation, and complex coacervation processes.…”
Section: Pectin-based Micro/nanoparticlesmentioning
confidence: 99%
“…Pectin from root and tuber crops as well as their food products and by-products have been extracted using different extraction methods (Table 2). Infante et al [21] reported the extraction of pectin from cassava bread using a boiling solution of oxalic acid and ammonium oxalate, while Coelho et al [22] extracted pectin from cassava residue using ammonium oxalate and further precipitated with ethanol. Menoli and Belia [23] also reported the precipitation of pectin from cassava galacturonic acid using a modified method [30] that involved saturated potassium acetate solution and 95% ethanol in a 4:1 ratio.…”
Section: Pectin Extractionmentioning
confidence: 99%
“…Studies showing this link include the evaluation of cassava and cocoyam root softening and implicates the role of endogenous (pectin methylestherase) and microbial enzymes which target cell wall materials [37,38]. To improve the bioavailability of beta carotene in animal feed, nano-particles containing the molecule was coated with pectin sourced from cassava residue [22]. The research showed promising strategy for neutraceutical administration of important bioactive compounds through mucosal surfaces.…”
Section: Application Of Root and Tuber Pectinmentioning
confidence: 99%